1970
DOI: 10.1017/s0021859600022899
|View full text |Cite
|
Sign up to set email alerts
|

A chemical study of soft fat in cross-bred pigs

Abstract: Iodine values, melting (slip) points and fatty acid analyses for back (' bung') and perinephric (kidney) fats from 114 pure and cross-bred pigs are reported.In most cases the effects of breed were small, but half-Hampshire crosses showed a high proportion of pigs producing abnormally soft and highly unsaturated fats, though others were normal.Although a general correlation existed between iodine value and melting-point the relationship broke down in some cases, and the ratio of monoene to saturated fatty acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…The iodine value is a measure of the degree of unsaturation present in the fat and therefore can used as an indicator of fat firmness. The results obtained in the present study did not exceed the maximum of 70 for the iodine value, index usually accepted by the industry as standard and considered as a reference for the fat to be classified as high-quality (Lea et al, 1970). The content of unsaturated fatty acids in the pig bellies is a major concern for the swine industry, since very soft bellies may become difficult for bacon slicing and cause the separation of fat from meat during slicing, and eventually may increase oxidation rate (National Pork Production Council, 1999).…”
Section: Resultssupporting
confidence: 61%
“…The iodine value is a measure of the degree of unsaturation present in the fat and therefore can used as an indicator of fat firmness. The results obtained in the present study did not exceed the maximum of 70 for the iodine value, index usually accepted by the industry as standard and considered as a reference for the fat to be classified as high-quality (Lea et al, 1970). The content of unsaturated fatty acids in the pig bellies is a major concern for the swine industry, since very soft bellies may become difficult for bacon slicing and cause the separation of fat from meat during slicing, and eventually may increase oxidation rate (National Pork Production Council, 1999).…”
Section: Resultssupporting
confidence: 61%
“…The C18:0 content (Wood et al, 1978) and relationship between MUFA and SFA (Lea, Swoboda, & Gatherum, 1970) have been considered as the best predictor of the SP. In general, a higher proportion of C18:0 and a lower proportion of C18:2n − 6 acids led to a harder fat (Lea et al, 1970).…”
Section: Slip Point Analysismentioning
confidence: 99%
“…Opposite to feeding lard, there is a marked decrease of PUFA concentration in barrows fed palm oil. In general, higher proportions of C18:0 and lower of C18:2n-6 led to a harder fat and higher melting point (Lea et al 1970). Lopez-Bote et al (2002) also found an increase on slip point when PUFA were substituted by MUFA.…”
Section: Sexmentioning
confidence: 91%